Obesity Risk Among Young Australian Women: A Prospective Latent Class Analysis. Issue 1 (22nd November 2019) - Hendryx, Michael; Chojenta, Catherine; Byles, Julie E.
Abstract : Objective: Prospective studies on obesity incidence specifically among young adults have not been reported. This study examined risks of obesity incidence over 19 years among young women without obesity at baseline. Methods: Women aged 18 to 23 years at baseline ( N = 8, 177) were followed up every 2 to 3 years to ages 37 to 42 using the Australian Longitudinal Study on Women's Health. A latent class analysis identified obesity‐risk classes based on time‐dependent measures of income, education, physical activity, sleep quality, dietary behavior, depression, stressful events, and social functioning. Cox proportional hazards regression models examined associations between incident obesity and latent classes, controlling for covariates. Results: Four latent classes were identified, including a lower‐risk referent class and classes characterized by poor exercise and diet, stress and low income, and multiple intermediate‐level risks. Compared with the referent, all three risk classes had significantly higher obesity risk, with the highest risk in the stress and low‐income group (hazard ratio = 2.22; 95% CI: 1.92‐2.56). Individual risks associated with obesity included lower education, stressful life events, and lower vigorous physical activity. Conclusions: Young women without baseline obesity were at risk of developing obesity when they experienced co‐occurring behavioral, socioeconomic, and psychosocial risks. Both latent classes and individual risk indicators offer insights into prevention strategies.